213k views
4 votes
The remainder obtained when

x^4 + 3x^2 - 2x + 2 is divided by (x + b) is the square of the
remainder obtained when x^2 – 3 is divided by (x + b). Find the values of b.​

1 Answer

3 votes

Use the polynomial remainder theorem: the remainder upon dividing a polynomial
p(x) by
x-c is
p(c).


(-b)^4+3(-b)^2-2(-b)+2=b^4+3b^2+2b+2


((-b)^2-3)^2=b^4-6b^2+9

Now


b^4+3b^2+2b+2=b^4-6b^2+9\implies9b^2+2b-7=0


\implies(9b-7)(b+1)=0


\implies b=\frac79\text{ or }b=-1

User Alexeyss
by
5.0k points